Power Factor Improvement of The Glenmore Sugar Industry Electrical System - Resi Dwi Jayanti Kartika Sari; Rini Nur Hasanah; Wijono Wijono (Widyagama University of Malang, 2022)
AbstractThis study discusses the improvement of the power factor in the Glenmore Sugar Industry electrical system. Low power factor can be caused by variations in inductive loads. This has an impact on large currents and high reactive power so that a black out can occur in the Glenmore Sugar Industry electrical system. Low power factor is corrected with the most effective Costum Power Devices, namely Static Var Compensator (SVC) and Static Synchronous Compensator (STATCOM). The evaluated and corrected load buses are those with low power factor.The simulation results show in the application of SVC for the lowest results, power factor increased from 0.76 to 0.78 with reactive power values in the range from + 1.6 to Ã¢â‚¬â€œ 0.64 MVAR. The power factor increased from 0.76 to 0.85 with reactive power values in the range from +4.9 to Ã¢â‚¬â€œ1.9 MVAR. And for the highest results, the power factor increased from 0.82 to 0.92 with reactive power values in the range from +3.9 to Ã¢â‚¬â€œ1.5 MVAR.The application of STATCOM can increase the power factor with reactive power values in the range from +4.9 to Ã¢â‚¬â€œ 0.994 MVAR, +1.6 to -0.32 MVAR and +3.9 to -0.7875 MVAR.Ã‚Â Keywords Ã¢â‚¬â€œ Power factor, SVC, STATCOM, Reactive power, Industry.